Changes in brain morphology in patients in the preclinical stage of idiopathic normal pressure hydrocephalus. Issue 6 (5th April 2019) - Suehiro, Takashi; Kazui, Hiroaki; Kanemoto, Hideki; Yoshiyama, Kenji; Sato, Shunsuke; Suzuki, Yukiko; Azuma, Shingo; Matsumoto, Takuya; Kishima, Haruhiko; Ishii, Kazunari; Ikeda, Manabu
Abstract : Background: Specific ventriculomegaly features, including tight high‐convexity and medial subarachnoid spaces, are found on magnetic resonance images in patients with idiopathic normal pressure hydrocephalus (iNPH). However, some healthy elderly individuals with no typical triad symptoms of iNPH also exhibit specific magnetic resonance image features of iNPH. Therefore, this study quantitatively clarified the brain morphology of suspected iNPH patients with no objective triad symptoms (iNPH‐NOS). Methods: We recruited patients with suspected iNPH and divided them into two groups based on their iNPH grading scale scores: the iNPH‐NOS group and the iNPH with apparent objective triad symptoms (iNPH‐AOS) group. Data for normal controls (NC) were taken from the database used in our previous study. We compared the relative volumes of ventricle systems (VS), Sylvian fissures (SF), and sulci at high convexity and the midline (SHM), adjusted by the intracranial volume, of the iNPH‐NOS, iNPH‐AOS, and NC groups. Additionally, we compared the relative volumes of VS, SF, and SHM in iNPH‐NOS patients between their first visit and follow‐up 1 year later. Results: Fifteen iNPH‐NOS patients and 45 iNPH‐AOS patients were recruited, and 24 NCs were found in the database. The relative volumes of VS and SF were significantly smaller than in NCs than in the iNPH‐NOS and iNPH‐AOS groups, and the relative volume of SHM was significantly larger in NCs. The relative volume of SHM was significantly larger in the iNPH‐NOS group than in the iNPH‐AOS group, but there were no significant differences in the relative volumes of VS and SF between these groups. In the iNPH‐NOS group, the relative volumes of VS and SF were significantly smaller at the first visit than 1 year later, whereas the relative volume of SHM was significantly larger. In 6 of 15 iNPH‐NOS patients, objective symptoms appeared during the observation period. Conclusions: Our results indicate that iNPH‐NOS patients were in the transitional stage between normal and iNPH‐AOS, both morphologically and clinically.